1998
DOI: 10.2214/ajr.171.6.9843287
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing contrast enhancement during helical CT of the liver: a comparison of two bolus tracking techniques.

Abstract: OBJECTIVE. The purposeof this studywas to evaluatea recentlydevelopedhardware and software system for CT scanning that generates images in real time and switches to heli cal CT scanning by either a visual cue or a region of interest (ROI) amplitude threshold. SUBJECTS AND METHODS. We randomlyandprospectivelydivided 120 abdominalCT examinations into three groups. Two groups received 75 ml of contrast agent at 1.5 ml/sec.Helical CT scanning began after visualization of the contrast bolus arrival in the hepatic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 22 publications
(17 reference statements)
0
19
0
Order By: Relevance
“…A few reports have shown that automatic bolus tracking is a suitable method for optimizing the contrast enhancement of the liver [15,21,22,23]. Studies comparing this technique with time-delay scanning showed significantly higher mean parenchymal enhancement using bolus tracking [15,21,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few reports have shown that automatic bolus tracking is a suitable method for optimizing the contrast enhancement of the liver [15,21,22,23]. Studies comparing this technique with time-delay scanning showed significantly higher mean parenchymal enhancement using bolus tracking [15,21,23].…”
Section: Discussionmentioning
confidence: 99%
“…They found that failures were more frequent especially in patients who are heavy and inpatients. Schweiger et al [22] even observed that hepatic scanning by visualizing the contrast bolus arrival would be better than by reaching a preset attenuation threshold; they, however, used an injection rate of only 1.5 ml/s. In the study by Dinkel et al [21] 1 of 39 patients did not reach the enhancement threshold of 31 HU.…”
Section: Discussionmentioning
confidence: 99%
“…With our imaging parameters, 120 kVp and 50 mA, the estimated absorbed skin and bone marrow doses to the patient are 396 and 120 mrad (3.96 and 1.20 mGy) for each second of exposure [4,15]. Although CTF time was relatively high for our patients compared with general abdominal intervention using CTF guidance at other institutions [5][6], it is likely a reflection of a combination of factors including the use of continuous CTF for lesion localization with and without abdominal wall compression, our lack of a compression device through which biopsies can be performed, and the difficult nature of cases described herein.…”
Section: Discussionmentioning
confidence: 99%
“…Accurately estimating the bolus arrival time and activating the control is a critical part of CTA (Hittmair, 2001;Paulson, 1998;Schweiger, 1998). In particular, the traditional constant speed control is extremely sensitive with respect to the activating time.…”
Section: Robustness On Starting Time (Threshold)mentioning
confidence: 99%